Effect of carbon and manganese content on the microstructure and mechanical properties of high manganese austenitic steel - Gürol U.; Can Kurnaz S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work, the influence of carbon and manganese on the microstructure and the mechanical properties of high manganese austenitic steel were investigated. Increased carbon and manganese content increased the grain size and the amount of carbides in the as-cast condition. The solution annealing fully dissolved the carbides in the alloys with lower carbon content (1wt%) and resulted in a homogeneous austenitic microstructure. The yield strength, ultimate strength, Charpy, and elongation were increased by the combination of carbon and manganese. Optimal results were obtained in the solution annealed 1.0C-17Mn alloy, respectively, 415.0±4.1MPa 865.6±1.5 MPa, 65.2±0.8%, and 258±3 J. The wear tests were performed under the loads of 2.5N, 5N, 10N and 15N with a ball-on-disc wear testing machine at constant speed of 0.2 ms-1 for sliding distance of 500m; it was revealed that 1C-21Mn alloy could be applied to relatively high-stress wear conditions while the 1.3C-17Mn alloy could be only used under low-stress wear conditions.